Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2024
DOI: 10.21203/rs.3.rs-3938899/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The causal relationship between gut microbiota and lower extremity deep vein thrombosis combined with pulmonary embolism

Qiyang Xu,
Jihong Fang,
Yi Wang
et al.

Abstract: Background Over the years, numerous studies have explored the relationship between gut microbiota and lower extremity deep vein thrombosis (LEDVT) and pulmonary embolism (PE). This study employed Mendelian randomization (MR) to investigate the causal link between gut microbiota and LEDVT combined with PE. Methods Human gut microbiota genome-wide association study (GWAS) summary data from the Mibiogen consortium (n = 18,340) were utilized. Summary-level data on LEDVT (2,116 cases and 359,078 controls) and LED… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…The genus Dialister has also been identified as a protective factor against arterial embolism and thrombosis in the lower extremity artery. For instance, dysbiosis in Dialister has been associated with various diseases, including thrombosis ( Pierre Lepargneur et al, 2006 ; Xu et al, 2024 ). Another study has also identified that an increase in Actinobacteria would decrease the risk of thrombosis ( Yang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The genus Dialister has also been identified as a protective factor against arterial embolism and thrombosis in the lower extremity artery. For instance, dysbiosis in Dialister has been associated with various diseases, including thrombosis ( Pierre Lepargneur et al, 2006 ; Xu et al, 2024 ). Another study has also identified that an increase in Actinobacteria would decrease the risk of thrombosis ( Yang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The genus Dialister has also been identified as a protective factor against arterial embolism and thrombosis in the lower extremity artery. For instance, dysbiosis in Dialister has been associated with various diseases, including thrombosis (Pierre Lepargneur et al, 2006;Xu et al, 2024). Another study has also identified that an increase in Actinobacteria would decrease the risk of thrombosis (Yang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%